การพัฒนากิจกรรมการเรียนรู้แบบ 4 MAT ที่เน้นการเชื่อมโยงคณิตศาสตร์กับชีวิตประจำวัน เรื่อง สถิติเบื้องต้น สำหรับนักศึกษาปริญญาตรี มหาวิทยาลัยราชภัฏมหาสารคาม - สุวรรณศรี พิชญ์ทิพา (Journal for Developing the Social and Community, 2016)
This research aimed to study develop a 4MAT learning activities management plan Focusing. on connecting to daily life entitled Introduction to Statistics of a couse on mathematics and Applied Statistics for Decision making for undergraduate students’ to compare pretest and Posttest learning achievement of the Students who Learned plan. Forty – five graduate student, who were taking a couse on mathematics and Applied statistics for decision making, were selected using a Cluster random sampling for the study. Research in struments included 5 plans of 4 MAT learning activities management focusing on connecting mathematics to daily life entiled introduction to Statistics, a 4-choice learning achievement test with Soitems, and a satisfaction guestionnaire with 20 items. The collected data were analyzed using a percentage, a mean, a standard deviation ; and dependent samples T – test was employed for testing a hypothesis (Independent Samples). The major findings were as Follows: 1. The developed Learning activities management plan had an efficiency of 88.16/84.39. 2. The student showed gains In learning achievement form before learning via the developed Plan at the .o5 level of significance. 3. The student indicated satisfaction with learning via The developed Plan as a whole of the most level.